Stereoselective cathodic synthesis of 8-substituted (1R,3R,4S)-menthylamines - Edinger, Carolin; Kulisch, Jörn; Waldvogel, Siegfried R. (Beilstein Journal of Organic Chemistry, 2015)
The electrochemical generation of menthylamines from the corresponding menthone oximes equipped with an additional substituent in position 8 is described. Due to 1,3-diaxial interactions a pronounced diastereoselectivity for the menthylamines is found.
Keywords: cathodic reduction; chiral amines; electrosynthesis; menthylamines; oximes